The electron-phonon interaction in a two dimensional electron gas - Hewett, Nicholas Peter (1988)
At low temperatures the predominant energy loss mechanism for a Joule-heated two dimensional electron gas (2DEG) in a metal oxide semiconductor field effect transistor (MOSFET) is by acoustic phonon emission. By very accurately measuring the temperature gradient developed along the silicon substrate the phonon emission has been investigated as a function of electron concentration, device power, magnetic field and temperature.